2011
DOI: 10.1186/1471-2334-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis manifesting with unilateral visual loss and hyponatremia: a case report

Abstract: BackgroundSyphilis is called the chameleon of the diseases due to its variety of its clinical presentations, potentially affecting every organ of the body. Incidence of this ancient disease is once again on the increase worldwide.Case presentationWe here report an unusual case of neurosyphilis manifesting with unilateral visual loss and hyponatremia. The patient also had primary syphilitic lesions and was concomitantly diagnosed with Human Immunodeficiency Virus (HIV), Hepatitis B Virus (HBV) and Hepatitis C V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Regarding the ophthalmological findings, an optic neuropathy usually, but not always, associates with a relative afferent pupillary defect. In other cases of syphilitic optic neuritis the afferent pupillary defect was also absent 10 11…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ophthalmological findings, an optic neuropathy usually, but not always, associates with a relative afferent pupillary defect. In other cases of syphilitic optic neuritis the afferent pupillary defect was also absent 10 11…”
Section: Discussionmentioning
confidence: 99%
“…Milger et al 5 reported a retropositive patient presenting with hyponatremia secondary to SIADH. However, the case in question had central hypothyroidism, making the diagnosis of SIADH questionable.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of VEP pathology suggested accompanying optic nerve involvement. Syphilis has been shown to affect cranial nerves as well as very rarely cause cavernous sinus syndrome or inappropriate antidiuretic hormone (ADH) syndrome (12,13 The first case was found to have asymmetrical pupil width as well as tonic pupil response (Figures 1, 2). The electroneugraphic evaluation found the nerve conduction velocities to be normal.…”
Section: Discussionmentioning
confidence: 99%